Computational modeling of carbon nanotubes for photoresistor applications. (March 2020) - Parvaiz, M. Shunaid; Shah, Khurshed A.; Dar, G.N.; Misra, Prabhakar
Abstract: In this paper, photoresistive properties in pristine and homogeneously boron and nitrogen doped semiconducting single-walled carbon nanotubes is studied. The calculations are based on density functional theory in combination with Non-Equilibrium Greens Function formalism. The resistance in the SWCNT models is found to decrease with the increasing flux levels. At low electrode voltages, nitrogen doped model shows more photoresistive effect while at high electrode voltages, the most significant photoresistive effect is found in boron doped model. The study reveals that the resistance of the proposed SWCNT systems is dependent on the light intensity, and the conventional boron and nitrogen doping increases the photoresistance by manifold. The models are promising for wide range of applications in the future electronic industry. Highlights: Photoresistance in semiconducting pristine, boron and nitrogen doped single walled carbon nanotube devices. The resistance in the CNT models decreases with the increasing flux levels from 1 to 1000 s −1  Å −2 . At low electrode voltage, nitrogen doped model shows maximum photoresistance. At high electrode voltages, boron doped model dominates the photoresistive effect.